SHIP CREW WELFARE RIGHTS BASED ON ARTICLE 151 PARAGRAPH 1 UU SHIPPING - Fadyl Shofwan Antista; Fitri Yanni Bactiar; Hotma P. Sibuea; Hedwig Adianto Mau; Yuhelson (Scholar Express Journals, 2023)
Protection of crew members is a law enforcement effort in analyzing the welfare of crew members' rights based on the provisions of Article 151 of Law Number 17 of 2008 concerning Shipping and as a manifestation of the protection of human rights based on the constitution. This is marked by placing the law in the highest position in an effort to protect the whole community, including crew members, from injustice and other interventions, as well as demanding responsibility and an active role from the government. This research uses a normative juridical method with library materials, such as books, laws and regulations and other library materials related to this research, and looks like cases that have occurred recently as a complement to this thesis research. Sources of data used are primary data and secondary data. As well as data analysis techniques using qualitative descriptive analysis to find answers precisely and accurately. Based on the results of the research, the position of ship crew is actually a citizen whose safety and rights must be protected like other citizens guaranteed by laws and regulations. Law Number 17 of 2008 concerning Shipping is a legal substance, in which enforcement requires responsibility from parties who have authority and is something that aims to protect legal subjects through applicable laws and regulations and is enforced with a sanction/penalty
Keywords: Legal Protection; Welfare; Ship Crew